(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The essay is based on philosophical aspects to support the idea of Divinity and God, starting, among other reflections, from amazing facts about the universe and human nature. This in order to support the conviction shared by many scientists that such wonders are not things of chance and chance. The way in which the knowledge of the universe, nature and the same way we have to know continues to expand, have revealed new dimensions of being that in other times were unimaginable. Beyond what is perceived by the senses, there are universes of units, relationships, mechanisms, structures and transformations that even the most illustrious minds and renowned scientists have been able to moderately encompass.